La protección de la integridad personal - Canosa Usera, Raúl (Revista de Derecho Político, 2017)
Resumen: El artículo pretende analizar la evolución de la protección de la integridad personal en España desde la aprobación de la Constitución de 1978 hasta el presente. En primer lugar, se aborda el contexto en el que la Constitución fue aprobada y las opciones que al constituyente se le abrían. Se destaca que por primera vez en España se reconocía un específico derecho a la integridad, lo que no es habitual, al lado de la tradicional prohibición de torturas y penas o tratos inhumanos o degradantes que arrancó ya con la constitución de 1812. Era necesario analizar la protección de la integridad en el Derecho Internacional de los derechos humanos que España ha incorporado a su Orden jurídico, así como la Carta de Derechos fundamentales de la Unión Europea Que sí proclama el derecho a la integridad. En este sentido es destacable como el Tribunal Europeo de Derechos Humanos ha inferido el derecho a la integridad de la forma más generosa a través de una interpretación evolutiva del derecho a la vida privada. Sin embargo, no es fácil determinar ni cuál es el bien jurídico protegido ni cuáles las posiciones iusfundamentales que contiene; es decir, qué se protege y cuáles son las situaciones de la vida cuya vulneración el titular del derecho puede defender, llegado el caso, activando la labor tutelar de los tribunales. Por ello ha sido fundamental también el intenso desarrollo legislativo que lo ha concretado en diversos sectores del ordenamiento así como las medidas de protección en favor de los más vulnerables. Summary: 1. The 1978 Context in which the right to integrity was recognized. 1.1 Overview of International Law and Foreign Constitutional Law. 1.2 The options of the Constituent Power in the process of drafting Article 15 of the Spanish Constitution. 2. The evolutionary interpretation of international law. 2.1 The extension of the protection field of Article 3 ECHR. 2.2 The inclusion of contents of the right to integrity into the right to respect for private life. a) Right to a criminal protection of the integrity. b) Right to authorize or refuse medical treatments. c) Right to sexual and reproductive life. The problem of abortion. d) Face to pollution. e) In the home. 3. Specific recognition of the right to integrity in the charter of fundamental rights of the European Union. 4. Determination of the fundamental positions under the right to integrity. 4.1 Procedural violation of the prohibition of torture. 4.2 Regarding health protection and in the heath field. a) Overlap with the right to health. b) Consent to medical treatment. c) Donations and transplants. d) Abortion as a potential exercise of the right to integrity by the pregnant woman. f) In the field of medical and scientific experiments. 4.3 Right to integrity against pollution. 4.4 Right to protection. 4.5 The guarantee to not suffer legal physical interventions and the exclusion of the indemnity guarantee. 4.6 In the special relationships of subjection. 4.7 In the labor market. 5. Conclusion: what object and what content? Abstract The article tries to analyze the evolution of the protection of integrity in Spain since the Constitution came into force in 1978. First of all, it is addressed the context in which the Constitution was approved as well as the options opened to Constituent Power. It is underlined that, for the first time in Spain, a specific right to integrity is declared, something unusual at that time, together with the traditional prohibition of torture and inhuman or degrading treatment or punishment, already introduced in the Constitution of 1812. It was necessary to analyze how the protection of integrity in International Law on Human Rights, as well as the right to the integrity of the person, proclaimed specifically in the Charter of Fundamental Rights of the European Union. In this sense, it is remarkable how the European Court of Human Rights has inferred a right to the integrity from the right to respect for private and family life, by interpreting evolutionarily the Convention. However, it is not easy to determine neither the object of the right to integrity nor what are the fundamental positions, the life situations, whose violation should permit person to claim in Courts of Justice, by activating their protective function. For the rest, it has also been crucial the intense legislative development that has implemented, in various sectors of the legal system, measures of protection in favor of the most vulnerable people.